Management teams and teaching staff: do they share the same beliefs about obligatory CLIL programmes and the use of the L1?. (4th March 2017) - Doiz, Aintzane; Lasagabaster, David
ABSTRACT: The popularity of CLIL (Content and Language Integrated Learning) continues to spread in education systems around the world. However, and despite the large number of studies recently published, we know little about how CLIL teachers and management teams feel regarding CLIL. In this paper, we analyse two contentious matters that require further analysis: (i) whether CLIL should be obligatory or optional for the students, and (ii) methodological issues such as the use of the students' linguistic repertoire. This study spans three years and examines the opinions and beliefs of CLIL teachers and management teams from three public schools located in the Basque Autonomous Community (Spain) through 24 discussion groups. The results reveal that, while the schools face similar problems in implementing CLIL (such as students' heterogeneity and the low level of English among some of them), the school management teams deal with these challenges differently and act on a trial and error basis. Although the management teams' decisions may not always be in line with their teaching staff's views, they do eventually manage to find some common ground.